LIBS as diagnostics of analytical chemistry for surface mapping of complex mixed samples simulating debris inside the TEPCO's Fukushima Daiichi Nuclear Power Plant (FDNPS) reactor cores - Almaviva, S.; Karino, T.; Akaoka, K.; Wakaida, Ikuo (Spectrochimica acta. Part B: Atomic spectroscopy, 2024)
The Nuclear Energy Agency (NEA) launched the Nuclear Education, Skills and Technology (NEST) Framework to pursue careers in the nuclear field, by exposing researcher working on these topics to international challenging project of real-world issue and by transferring the knowledge and expertise accumulated in the current generation to them through hands-on training. In this framework the 2022 edition of the NEST project offered a training educational period at the Collaborative Laboratories for Advanced Decommissioning (CLADS) located at Tomioka, Futaba District, in the Fukushima prefecture (Japan). Among the research sectors active at CLADS there is the application and development of the LIBS technique as diagnostics of analytical chemistry aiming at characterizing the debris inside the Tokyo Electric Power Company (TEPCO)’s FDNPS reactor cores after the tsunami of March 2011, which destroyed three of the six reactors of the plant. These debris need to be chemically characterized with techniques suitable to be implemented in compact, remote and radiation resistant devices, due to the residual radioactivity of the cores. The present study shows the results in realizing chemical bi-dimensional maps of samples in the form of compressed tablets of mixed oxides, with a complex distribution and concentration of chemicals simulating these debris. The results allowed to create detailed maps of the samples, with spatial resolution down to 0.5 mm and an excellent correspondence between the real spatial distribution of the materials and that reconstructed by LIBS. Moreover, it was found a good correspondence between the nominal concentration of the chemicals and the concentration estimated by using LIBS. This study shows the potentialities of LIBS in the realization of chemical maps on samples of interest for FDNPS, providing multi-elemental images of the samples under analysis. [Display omitted] •Elemental imaging using LIBS.•LIBS analysis of samples with complex composition of different materials.•LIBS study of sample of interest in nuclear fission technology.